Penerapan Kode Etik Profesi Auditor Dalam Menjaga Kualitas Audit Studi Kasus Kantor Akuntan Publik Drs. Rinaldi Munaf - Yarnidar Gulo; Nufidatul Mahmudah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The implementation of a professional code of ethics is essential in ensuring audit quality, as it enables auditors to provide accurate assessments that faithfully reflect actual conditions. Throughout the audit process, auditors often encounter various challenges in adhering to ethical principles, including client pressure and potential conflicts of interest that may test their commitment to professional ethics. This study aims to explore auditors' perspectives on the implementation of the professional code of ethics in maintaining audit quality. A descriptive qualitative approach was employed through interviews with three informants at the Public Accounting Firm (KAP) of Drs. Rinaldi Munaf, consisting of a senior auditor, a junior auditor, and a partner. The findings indicate that effective implementation of the professional code of ethics plays a crucial role in maintaining audit quality. All informants agreed that adherence to the code of ethics is the primary foundation for producing high-quality, objective, and reliable audits. Audits conducted with honesty, diligence, and reliability were identified as key indicators of the successful application of ethical principles within the auditing profession. The study concludes that the consistent implementation of the professional code of ethics not only enhances audit quality but also strengthens public trust in the auditing profession.